Hubungan Peran Ketua Tim dengan Kinerja Perawat Pelaksana dalam Pendokumentasian Keperawatan di Rumah Sakit Bhayangkara Kota Bengkulu - Fitriana Fitriana; Mariza Arfianti; Yogi Yogi; Ova Ova; Rachel Rachel (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Nursing is a profession that provides nursing care to patients in hospitals 24 hours a day. Since nurses make up the majority of the hospital workforce, hospitals are expected to have high-performing nurses to support the hospital’s overall performance and ensure patient satisfaction with the services provided. Nursing documentation consists of records containing all the information necessary to determine nursing diagnoses, develop nursing care plans, implement nursing interventions, and evaluate nursing actions; these records must be prepared correctly and be morally and legally accountable. This study aims to: determine the relationship between the role of the team leader and the performance of practicing nurses in nursing documentation. This is an analytical observational study using a cross-sectional design involving 44 nurses working at Bhayangkara Hospital in Bengkulu. Sampling was conducted using probability sampling with a total sampling approach. The research instrument used was a questionnaire. The results of the chi-square test yielded a value of ρ = 0.004 and α = 0.05; since ρ ≥ α, it was concluded that there is a relationship between the role of the team leader and the performance of practicing nurses in nursing documentation at Bhayangkara Hospital in Bengkulu. Therefore, it is important for team leaders to play a role in improving the performance of practicing nurses in performing documentation correctly.